2015
DOI: 10.1007/s11934-015-0523-9
|View full text |Cite
|
Sign up to set email alerts
|

Update on Testosterone Replacement Therapy in Hypogonadal Men

Abstract: Late-onset male hypogonadism has long been recognized as a treatable medical condition; however, misconceptions about the use of testosterone replacement therapy (TRT) have often led urologists away from its more mainstream use. This paper aims to bring the reader up-to-date on the current understanding of TRT, starting with when and who to treat. Various formulations of TRT, each with its own risks and benefits, are also detailed. Finally, a comprehensive analysis of the current literature's views into the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 99 publications
(164 reference statements)
0
4
0
1
Order By: Relevance
“…A small number of studies have suggested that some of these symptoms may be reversed by testosterone or estrogen therapy. 28,31 Our criteria for frail health differed from those of Fried et al 6 and from those reported in the St Jude Lifetime Cohort Study. 5 The major limiting factor is that the fifth component of the frailty phenotype, the 'self-reported exhaustion' defined by Fried et al, 6 was missing since questionnaires to classify self-reported exhaustion were not included.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…A small number of studies have suggested that some of these symptoms may be reversed by testosterone or estrogen therapy. 28,31 Our criteria for frail health differed from those of Fried et al 6 and from those reported in the St Jude Lifetime Cohort Study. 5 The major limiting factor is that the fifth component of the frailty phenotype, the 'self-reported exhaustion' defined by Fried et al, 6 was missing since questionnaires to classify self-reported exhaustion were not included.…”
Section: Discussionmentioning
confidence: 83%
“…Myeloablative HDTx regimens, irrespectively of the use of TBI, are known to be associated with high-risk gonadal toxicity. 28,29 Many symptoms of hypogonadism are similar to agerelated changes. It may be difficult to conclude if the association of hormonal replacement therapy and frail health indicates simply a more toxic cancer therapy that the survivors have received or an independent effect on frailty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the studies included in our analysis reported no or minimal side effects after E. longifolia treatment [26,29,30]. This is of interest because TRT, representing the first therapeutic option in the case of hypogonadism, has been associated with the presence of side effects, such as polycythaemia, fluid retention, testicular atrophy, prostate enlargement, congestive heart failure, and obstructive sleep apnea [47]. Furthermore, in males and females, E. longifolia does not negatively affect AST/ALT or body weight, further supporting safe treatment with E. longifolia [48].…”
Section: Discussionmentioning
confidence: 93%
“…İntramusküler preparatların absorbsiyon profilleri farklıdır. Bu nedenle genellikle preparatın çeşidine göre değişen haftalık sürelerde uygulanırlar 22 . Transdermal preparatların günde tek sefer kullanım kolaylığı, uygulama rahatlığı ve daha düşük pik ve düşüşlere yol açma avantajları vardır.…”
Section: Testosteron Replasmanıunclassified